2011
DOI: 10.1088/0953-4075/44/2/025502
|View full text |Cite
|
Sign up to set email alerts
|

Teleportation of the one-qubit state in decoherence environments

Abstract: We study standard quantum teleportation of one-qubit state for the situation in which the channel is subject to decoherence, and where the evolution of the channel state is ruled by a master equation in the Lindblad form. A detailed calculation reveals that the quality of teleportation is determined by both the entanglement and the purity of the channel state, and only the optimal matching of them ensures the highest fidelity of standard quantum teleportation. Also our results demonstrated that the decoherence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…[10,11], in which the authors argued that the entanglement is a genuine resource for teleportation even if noises are involved, however, our results presented in figure 1 revealed that their statement is not universal. In fact, entanglement of the channel state is the prerequisite but not the only essential quantity for predicting fidelity of quantum teleportation [16,25]. This finding will be further confirmed in the following discussions with other types of initial atomic states.…”
mentioning
confidence: 67%
“…[10,11], in which the authors argued that the entanglement is a genuine resource for teleportation even if noises are involved, however, our results presented in figure 1 revealed that their statement is not universal. In fact, entanglement of the channel state is the prerequisite but not the only essential quantity for predicting fidelity of quantum teleportation [16,25]. This finding will be further confirmed in the following discussions with other types of initial atomic states.…”
mentioning
confidence: 67%
“…c 1, k and c 2, k describe respectively, decay and excitation processes of the k th qubit due to its interaction with the reservoir, with being the average thermal photons in the reservoir, and γ k the damping rates which will taken to be equal in the following, i.e., γ 1  =  γ 2  =  γ . Similar models in the study of state transfer 52 and quantum teleportation 53 have already been exploited.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all the states that are entangled can be used for teleportation with average fidelity (see sections below) better than that achievable via classical communication alone [5,6], and the average fidelity is even not a monotone function of the degree of entanglement of the channel state. This seemingly counterintuitive phenomenon has been noticed by a number of authors [7][8][9][10][11]. Particularly, there are situations in which the channel states possess greater amount of entanglement with however the average fidelity cannot exceed the classical limiting value of 2/3 [11].…”
Section: Introductionmentioning
confidence: 96%
“…This seemingly counterintuitive phenomenon has been noticed by a number of authors [7][8][9][10][11]. Particularly, there are situations in which the channel states possess greater amount of entanglement with however the average fidelity cannot exceed the classical limiting value of 2/3 [11].…”
Section: Introductionmentioning
confidence: 96%